The crimson flame - Dixon, Franklin W.; Frame, Paul 1913- (New York Simon & Schuster, 1983)
The Hardy brothers travel to an Arizona ranch and eventually, Thailand in pursuit of jewel thieves who have stolen a priceless ruby.
Keywords: Mystery and detective stories